Long-Term and Intergenerational Effects of Education Evidence from School Construction in Indonesia - Akresh, Richard (The World Bank, 2021)
This paper studies the long-term and intergenerational effects of the 1970s Indonesian school construction program, which was one of the largest ever conducted. Exploiting variation across birth cohorts and districts in the number of schools built suggests that education benefits for men and women persist 43 years after the program. Exposed men are more likely to be formal workers, work outside agriculture, and migrate. Men and women who were exposed to the program have better marriage market outcomes with spouses that are more educated, and households with exposed women have improved living standards and pay more government taxes. Mother's program exposure, rather than father's, leads to education benefits that are transmitted to the next generation, with the largest effects in upper secondary and tertiary education. Cost-benefit analyses show that school construction leads to higher government tax revenues and improved living standards that offset construction costs within 30-50 years